2021
DOI: 10.1002/jsfa.11464
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of protein isolates from rohu (Labeo rohita) processing waste through incorporation into fish sausages; quality evaluation of the resultant paste and end product

Abstract: BACKGROUND: Fish processing waste could be valorized by recuperating the nutrients for human consumption. Employing a suitable process would address the pollution problems associated with its dumping and would contribute to food security. In this study, protein isolates obtained from rohu (Labeo rohita) processing waste through the pH shift process (pH 13.0) were valorized through incorporation into pangasius (Pangasius pangasius) mince sausages (0.0, 50, 100, 250, and 500 g kg −1 ). These sausages were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…He reported that the supplementing biscuits with protein concentrate did not show significant effect on sensory attributes of the biscuits and utilization of fish protein concentrate made from tilapia by‐products is a solution to fish waste disposal problems. Surasani et al (2022), also found that supplementing fish sausages with rohu protein isolates did not cause significant changes in its sensory characteristics and acceptability, indicating the potential application of proteins recovered from low‐cost complex raw material in foods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…He reported that the supplementing biscuits with protein concentrate did not show significant effect on sensory attributes of the biscuits and utilization of fish protein concentrate made from tilapia by‐products is a solution to fish waste disposal problems. Surasani et al (2022), also found that supplementing fish sausages with rohu protein isolates did not cause significant changes in its sensory characteristics and acceptability, indicating the potential application of proteins recovered from low‐cost complex raw material in foods.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few reports are available on utilization of recovered proteins and by-products from fish processing waste for human edible purpose (Shaviklo, 2008;Singh et al, 2021;Surasani, 2017;Surasani et al, 2022;Surasani, Raju, Shafiq, Chandra, & Lakshmisha, 2020;Surasani, Raju, Singh, & Joshi, 2021;Surasani, Singh, et al, 2019), which necessitates the further research in this area.…”
Section: Novelty Impact Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Indian freshwater aquaculture is mainly dominated by carp species (Rasal and Sundaray, 2020). Among these, Indian major carps (IMCs), catla, Catla catla, rohu, L. rohita, and mrigal, Cirrhinus mrigala, are the most important and prime cultivable fish species in India (Surasani et al, 2021) due to their high customer demand and economic value. IMCs contribute more than 70% of freshwater production in India (DoF, 2020).…”
Section: Introductionmentioning
confidence: 99%